Kinetic modeling of the steam reforming of light hydrocarbon mixture from waste resources: Effects of gas composition on hydrogen production - Woo, Yesol; Park, Jae Min; Bae, Jong Wook; Park, Myung June (International Journal of Hydrogen Energy, 2023)
Steam reforming of a light hydrocarbon mixture, which might be produced during the pyrolysis of waste resources, was experimentally conducted over a commercial Ni-based catalyst. Two different gas compositions were considered as simulated gases to utilize waste resources, and kinetic data were generated at a variety of temperatures, space velocities, and steam-to-carbon ratios to develop a kinetic model by fitting the experimental data. Experimental observations indicated that the inclusion of higher chains resulted in low methane conversion compared to those of the other chains, and the model demonstrated that the increased hydrogen production rate by higher chains enhanced methanation, resulting in a decreased methane conversion. The increased fraction of higher chains decreased the steam-to-carbon ratio for methane, resulting in a decreased methane conversion. Further analysis showed that despite the decrease in methane fraction, hydrogen production could be increased by 4% with a 10% methane fraction in the light hydrocarbon mixture, indicating that the direct reforming of a light hydrocarbon mixture from waste resources with no pre-reforming might be feasible.
Keywords: Different gas; Gas compositions; Hydrocarbons mixtures; Kinetic models; Light hydrocarbon; Light hydrocarbon mixture; Methane conversions; Ni-based catalyst; Steam-to-carbon ratio; Waste resources; Hydrogen production; Kinetic model; Light hydrocarbon mixture; Steam reforming; Waste resources